Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy